2015
DOI: 10.1080/09205063.2015.1008882
|View full text |Cite
|
Sign up to set email alerts
|

Dual growth factor-immobilized microspheres for tissue reinnervation:in vitroand preliminaryin vivostudies

Abstract: Growth factors (GFs) (basic fibroblast growth factor (bFGF) and/or nerve growth factor (NGF))-immobilized polycaprolactone (PCL)/Pluronic F127 microspheres were prepared using an isolated particulate-melting method and the sequential binding of heparin and GFs onto the microspheres. The GFs immobilized on the microspheres were released in a sustained manner over 28 days, regardless of GF type. From the in vitro culture of muscle-derived stem cells, it was observed that the NGF-immobilized microspheres induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…This could be due to a very low quantity of growth factors bound to the surface by weak interactions, the degradation of NGF and BDNF because they were not established (Lam et al, 2001). These findings are supported by Kim et al who found that microspheres loaded with heparin bound significantly more bFGF and NGF than microspheres without heparin (Kim et al, 2015). Moreover, Johnson et al also incorporated heparin into hydrogels to stabilise both NGF and BDNF (Johnson et al, 2015).…”
Section: Discussionmentioning
confidence: 87%
“…This could be due to a very low quantity of growth factors bound to the surface by weak interactions, the degradation of NGF and BDNF because they were not established (Lam et al, 2001). These findings are supported by Kim et al who found that microspheres loaded with heparin bound significantly more bFGF and NGF than microspheres without heparin (Kim et al, 2015). Moreover, Johnson et al also incorporated heparin into hydrogels to stabilise both NGF and BDNF (Johnson et al, 2015).…”
Section: Discussionmentioning
confidence: 87%
“…The individual effect of bFGF and NGF has been validated in our prior studies [33,84]. Studies have indicated that co-administration of NGF and bFGF together could synergistically promote tissue reinnervation and neural differentiation, compared with bFGF and NGF alone [85,86]. In this study, we evaluated the effectiveness of dual GF administration for the first time in peripheral nerve injuries, and focused on showing how HP hydrogel can augment this therapy strategy.…”
Section: Discussionmentioning
confidence: 91%